PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG MANAJEMEN HIPERTENSI MELALUI LATIHAN SLOW DEEP BREATHING - Dzakiya Diena Karimah; Salsabila Saufia Aura Sadin; Afinda Krisdeana; Luthfi Maulana Ibrahim; Hanifah Eka Ningtyas; Ghina Attila Setya Maharani; Siti Mulyati; Hanifa Nurmajid; Bagas Haidir Sakti; Halimah Muhtar; Indah dewi nurjanah; Khayla Febriannisa'; Wahyuni Wahyuni; Beti Kristinawati (Universitas Muhammadiyah Surakarta, 2026)
Hypertension is a non-communicable disease that is commonly found in the community and has the risk of causing serious complications if not treated properly. One of the effective non-pharmacological methods to lower blood pressure is (slow deep breathing). However, education and practice of this technique is still limited at the community level. This community service activity aims to increase community knowledge about slow deep breathing techniques as an effort to control hypertension. The method used is education and training directly to the community in Manang Village, Grogol District, Sukoharjo Regency. Evaluation was carried out by comparing the results of the pre-test and post-test of the participants. The results of the activity showed a significant increase in participants' understanding, with an increase in the percentage of correct answers in the post-test compared to the pre-test. Participants also showed high enthusiasm during discussion and practice sessions. This activity succeeded in improving public health literacy related to hypertension management and encouraging sustainable independent habits in slow deep breathing practice. The conclusion of this activity shows that community-based participatory education is effective for improving knowledge and skills in hypertension management. It is recommended that similar activities be carried out periodically and involve local health cadres to maintain program sustainability.